PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENDUKUNG EKONOMI MIKRO DAN KECIL: STUDI KASUS KJKS BMT-UGT SIDOGIRI - Firdausiah, Nuri (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
This study examines the important role of economic activities in people's daily lives and the role played by banking institutions in the context of the economy. In addition, the study highlights the development of Islamic banking as a coveted alternative for Muslims in the financial system. The research explains that Islamic banking focuses on sharia principles, particularly the principle of profit sharing, as a fair and usury-free alternative.Furthermore, the research describes the role of the Integrated Self-Help Enterprise (BMT) as an Islamic microfinance institution that assists the economy of micro and small entrepreneurs. In this context, profit sharing is the main characteristic that distinguishes the Islamic financial system from the conventional one. The research highlights the importance of following sharia provisions in the operational activities of Islamic financial institutions and the role of the Indonesian Ulema Council (MUI) in determining the halalness of transactions.It also presents a case study of KJKS BMT-UGT Sidogiri, highlighting mudharabah financing as a high-risk product and issues related to profit projection. The findings in this study indicate the need for further research in this context, with the aim of improving the understanding and implementation of sharia principles in Islamic financial institutions and supporting the development of micro and small economies in a fair and sustainable manner.